Mapping of a gene involved in distorted segregation in interspecific tomato populations - Barrantes Santamaría, Walter (2020)
Introduction. Distorted segregation (SD) occurs when the expected genotypes do not correspond to those observed, which favors single parent alleles. This phenomenon was observed in intermediate populations from the cross between Solanum pimpinellifolium and the Moneymaker cultivar of Solanum lycopersicum, developed during the construction process of a library of introgression lines. Objective. Obtain informative recombinants that allow physically mapping a region with SD associated with the wild Solanum pimpinellifolium species. Materials and methods. The research was carried out at the Institute of Molecular and Cellular Biology of Plants (IBMCP) attached to the Higher Council for Scientific Research (CSIC) based at the Universidad Politecnica de Valencia, Spain. A population of 2000 plants was screened to identify recombinants in that region, with a modification of the high-resolution melting technique (HRM-Multiplex). These recombinants were self-fertilized, and through the Chi-square statistic it was determined whether SNP markers identified within the target region had a normal (1:2:1) or distorted segregation for each informative recombinant selected. Results. Fifty-four informative recombinants were generated and identified, grouped into 10 bins according to the physical recombination site. It was possible to delimit the region with distorted segregation until obtaining a final size of 84 Kb, which was located at the distal end of the long arm of chromosome 4. This region contains a large number of genes, some of which are related to fertilization processes, sterility and cell division among others, which could be related to the studied phenomenon. Conclusion. A gene was found, that causes a segregation distortion in an interval of 84 Kb and possibly is the gene Ge described by Rick in 1966.